Socio-Cultural Explanation of Newborn Child Health and Illness: An Anthropological Study on The Practice of Ethnomedicine in the Context of Rural Child - Akter , Hiramony (South Asian Journal of Social Sciences and Humanities, 2025)
The health of infants in rural areas is influenced by factors like medicine as well as traditional  and cultural beliefs. The study examines the impact of local beliefs and practices on the health  and well-being of newborns in Bhangura village, as well as the significance of ethnomedicine  in caring for newborns within the village. Based on interviews, the study suggests that many  caregivers act and seek healthcare based on the cultural belief that illness in a newborn was  triggered by an evil force. Herbal remedies, rituals and massage are usually used first and only  biomedical health care is considered when the traditional ways fail. A person’s decision about  medical care is influenced by how accessible it is, its cost, their trust in traditional healers and its suitability with their culture. It is suggested by the study that both ethnomedicine and  biomedicine can work together and support newborn health by implementing related policies.  This research indicates that how medical support is provided to newborns in rural areas should  be influenced by cultural factors for good outcomes.
Keywords: Newborn health; Ethnomedicine; Socio-cultural beliefs; Rural healthcare; Neonatal illness; medical pluralism.